2018
DOI: 10.1002/mnfr.201700810
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Protects Pancreatic β‐Cells Against Oxidative Stress‐Induced Apoptosis by Inhibiting Both Intrinsic and Extrinsic Pathways in Insulin‐Deficient Diabetic Mice

Abstract: Taken together, our study provides insights into the underlying mechanisms through which naringin protects the pancreatic β-cells against oxidative stress-induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
(85 reference statements)
1
24
0
1
Order By: Relevance
“…Naringin, as reported by Sahnoun et al (2017), showed an excellent inhibition for α-amylase and α-glucosidase enzyme, with IC 50 values of 8.0 μM and 0.55 μM, respectively. Lim et al (2018) studied the protective effects and molecular mechanisms of naringin in diabetic mice. The results showed that this flavanone ameliorated hyperglycemia and protected STZ-induced β-cell death by inhibiting both intrinsic and extrinsic apoptotic pathways.…”
Section: Naringeninmentioning
confidence: 99%
“…Naringin, as reported by Sahnoun et al (2017), showed an excellent inhibition for α-amylase and α-glucosidase enzyme, with IC 50 values of 8.0 μM and 0.55 μM, respectively. Lim et al (2018) studied the protective effects and molecular mechanisms of naringin in diabetic mice. The results showed that this flavanone ameliorated hyperglycemia and protected STZ-induced β-cell death by inhibiting both intrinsic and extrinsic apoptotic pathways.…”
Section: Naringeninmentioning
confidence: 99%
“…Naringin also has a protective effect on β-cells due to its capacity to prevent apoptosis through the inhibition of both the intrinsic (mitochondria-mediated) and extrinsic (death receptor-mediated) pathways. These anti-apoptotic effects are associated with a reduction in ROS and inflammatory cytokines [63].…”
Section: Recent Preclinical Advances In the Anti-diabetic Actions Of mentioning
confidence: 99%
“…[10][11][12] Naringin regulates oxidative stress-induced apoptosis and the inflammatory response through intrinsic and extrinsic pathways, thereby effectively protecting pancreatic b-cells in insulin-deficient diabetic mice. 13 Naringin also ameliorates arsenicinduced cardiotoxicity, which is related to the Nrf2/HO-1 pathway. 14 Previously, we reported the effect of naringin on the inflammatory response of SIMD and its molecular mechanism.…”
Section: Introductionmentioning
confidence: 96%